2022
DOI: 10.3390/challe13010010
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19-Related Job Demands and Resources, Organizational Support, and Employee Well-Being: A Study of Two Nordic Countries

Abstract: The purpose of this study is to examine how COVID-19-related job demands and resources have been associated with employee well-being in Nordic countries across specific occupational groups. The study investigated four occupational groups: (1) professional, scientific, and technical occupations in Norway (n = 301); (2) teachers in Finland (n = 315); (3) health and social service occupations in Norway (n = 267); and (4) geriatric nurses in Finland (n = 105). Hypotheses were tested using two-step hierarchical reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 88 publications
(134 reference statements)
1
7
1
Order By: Relevance
“…It should be noted that these findings were done in a Norwegian sample of insurance workers. Although only 3% of this sample had the experience of working from home before the pandemic, indicating a new situation for most of the employees, it has been suggested that the pandemic situation has been less severe in Nordic countries like Norway with less stringent restrictions during the pandemic and a strong welfare model securing the health and wellbeing of the employees (Lilja et al, 2022 ).…”
Section: Discussionmentioning
confidence: 96%
“…It should be noted that these findings were done in a Norwegian sample of insurance workers. Although only 3% of this sample had the experience of working from home before the pandemic, indicating a new situation for most of the employees, it has been suggested that the pandemic situation has been less severe in Nordic countries like Norway with less stringent restrictions during the pandemic and a strong welfare model securing the health and wellbeing of the employees (Lilja et al, 2022 ).…”
Section: Discussionmentioning
confidence: 96%
“…Technology and online work provide the freedom to plan work, which in turn, supports work–life balance and work engagement [ 44 ]. Organisational support and one’s positive attitude towards online work are essential, as they may help to maintain work engagement [ 44 , 45 ]. Additionally, media can support local people in challenging situations, as found in this study which investigated COVID-19 related news published in one local newspaper in Northernmost Finland.…”
Section: Discussionmentioning
confidence: 99%
“…Failure of educational organizations to promote supportive environments may create an unrelenting environment, reducing resilience and affecting burnout indirectly. These findings suggest that organizations should intervene quickly during challenging times to develop perceptions of support that may act as a supportive asset for sustaining employee well-being and promoting resilience (Lilja et al, 2022). Second, the sole use of self-report survey measures to understand teachers' perceived stress may have biased the results due to shared-method variance.…”
Section: Discussionmentioning
confidence: 99%